Comparison of enhanced potency inactivated poliovirus vaccine (EIPV) versus standard oral poliovirus vaccine (OPV) in thai infants - Sriluck Simasathien (2018)
Enhanced potency inactivated poliovirus vaccine (EIPV), combined with diphtheria-tetanus-pertussis (DTP) vaccine, was compared with oral poliovirus vaccine (OPV) regarding immunogenicity in Thai infants, vaccinated at 2, 4 and 6 months of age. EIPV induced significantly higher seroconversion rates than OPV to all 3 poliovirus types after the second and third immunization. After 3 doses of each vaccine, at 7 months of age, all infants receiving EIPV proved seropositive for poliovirus type 1, type 2 and type 3 neutralizing antibodies, whereas of those receiving OPV, 9% remained seronegative (titre < 1:4) for type 1 (p = 0.0042) and 11% for type 3 (p =0.0013). All participating children were given an additional dose of OPV at the age of 9 months and tested again at 12 months of age. At that point, virtually all infants had poliovirus neutralizing antibodies, but the geometric mean titres to each poliovirus type were significantly higher in the vaccinees who had received EIPV. It is concluded that the greater immunogenicity of EIPV vis-àvis 3 doses of OPV may be biologically significant for protection against poliovirus types 1 and 3 in countries where cases of poliomyelitis occur in young children. These findings warrant considering EIPV, alone or in combination with OPV, for an immunization programme in Thailand and similar countries in the future. © 1994 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.